2015
DOI: 10.1515/bvip-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrathecal Administration of Ketamine HCl in Young Calves: A Clinical Trial

Abstract: The purpose of the study was to investigate the clinical, biochemical, and cardiovascular effects of intrathecal (IT) administration of ketamine HCl in calves. The study was performed on seven Simmental and three Montofon calves, 1.70 ± 1.16 weeks old, weighing approximately 37 kg, undergoing surgical procedures including femur fracture repair (one case), atresia anus (five cases), prolapsed rectum (one case), suturing on rear limbs (two cases), and urethrostomy (one case). After administering IT ketamine HCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this study, anaesthesia scores in the isoflurane group showed a better analgesic appearance than the sevoflurane group, while painful stimuli were performed every 15 min with a 23-gauge needle to evaluate superficial and deep pain in the tail and limbs. It has been stated that an increase of 20% or more in HR, SABP, DABP, MABP, RR, PR compared to baseline values during operation can be considered as an intraoperative pain symptom [23], but no increase in HR, SABP, DABP, MABP, RR, PR measurements was observed. No evidence of intraoperative pain in this regard, nor any other symptoms indicating pain, were found.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, anaesthesia scores in the isoflurane group showed a better analgesic appearance than the sevoflurane group, while painful stimuli were performed every 15 min with a 23-gauge needle to evaluate superficial and deep pain in the tail and limbs. It has been stated that an increase of 20% or more in HR, SABP, DABP, MABP, RR, PR compared to baseline values during operation can be considered as an intraoperative pain symptom [23], but no increase in HR, SABP, DABP, MABP, RR, PR measurements was observed. No evidence of intraoperative pain in this regard, nor any other symptoms indicating pain, were found.…”
Section: Discussionmentioning
confidence: 99%
“…IT anesthesia is a simple and more economic approach to anesthesia as it can be administered without the equipment and devices required for inhalation anesthesia, but the experience during administration can be viewed as a disadvantage [1,3] . IT anesthesia is preferred to general anesthesia for hind limb surgery, flank surgery, ovariohysterectomy, cesarean section and tail surgery in many animal species [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%